Freeze-Thaw Performance of Silt Sand Treated with Lignin - Fu Zhu; Jiayu Li; Wenhao Jiang; Shuang Zhang; Weizhi Dong (Advances in Civil Engineering)
In cold regions, freeze-thaw action poses a significant hazard to road engineering. In order to avoid the adverse effects of inorganic materials on soil modification, we applied lignin, which is an environmentally friendly and organic polymer, to improve the silt sand from cold regions. The significance of this study is to facilitate the better application of lignin. The macroscopic engineering properties of the soil showed that, before freeze-thaw, as the lignin content increased, thermal conductivity and permeability decreased, pH first increased rapidly and then stabilized between 10 and 11, and dynamic resilient modulus first increased then decreased; after freeze-thaw, as lignin content increased, thermal conductivity and permeability decreased, and dynamic resilient modulus first increased then decreased. The freeze-thaw action reduced the thermal conductivity and dynamic resilient modulus of silt sand treated with lignin and increased its permeability. The test results of soil microstructure indicated that, before freeze-thaw, the silt sand and silt sand treated with lignin were structurally compact; after freeze-thaw, the silt sand showed numerous cracks and pores and had a loose soil structure, whereas the silt sand treated with lignin showed fewer cracks and pores, and its soil structure was more compact under the encapsulation and filling action of cementitious materials. No new chemical elements, mineral components, or functional groups were produced when lignin was mixed with silt sand. The mechanism by which lignin improved the macroengineering properties of silt sand involved the cementitious material produced by the interaction between lignin and soil minerals, which encapsulated the soil particles and filled the interparticle pores. Research results can provide a theoretical reference for engineering application of lignin in cold regions.